Thioredoxin as a putative biomarker and candidate target in age-related immune decline. (11th August 2014) - Griffiths, Helen R.; Bennett, Stuart J.; Olofsson, Peter; Dunston, Christopher R.
Abstract : The oxidoreductase Trx-1 (thioredoxin 1) is highly conserved and found intra- and extra-cellularly in mammalian systems. There is increasing interest in its capacity to regulate immune function based on observations of altered distribution and expression during ageing and disease. We have investigated previously whether extracellular T-cell or peripheral blood mononuclear cell Trx-1 levels serve as a robust marker of ageing. In a preliminary study of healthy older adults compared with younger adults, we showed that there was a significant, but weak, relationship with age. Interestingly, patients with rheumatoid arthritis and cancer have been described by others to secrete or express greater surface Trx-1 than predicted. It is interesting to speculate whether a decline in Trx-1 during ageing protects against such conditions, but correspondingly increases risk of disease associated with Trx-1 depletion such as cardiovascular disease. These hypotheses are being explored in the MARK-AGE study, and preliminary findings confirm an inverse correlation of surface Trx-1 with age. We review recent concepts around the role of Trx-1 and its partners in T-cell function on the cell surface and as an extracellular regulator of redox state in a secreted form. Further studies on the redox state and binding partners of surface and secreted Trx-1 in larger patient datasets are needed to improve our understanding of why Trx-1 is important for lifespan and immune function.